Getting the unemployed back to work: the role of targeted wage subsidies - Brian Bell; Richard Blundell; John Van Reenen (Institute for Fiscal Studies (IFS), 1999)
This paper examines alternative approaches to wage subsidy programmes. It does this in the context of a recent active labour market reform for the young unemployed in Britain. This Óew DealÔ reform and the characteristics of the target group are examined in detail. We discuss theoretical considerations, survey the existing empirical evidence and propose two strategies for evaluation. The first suggests an expost \~Nrend adjusted diÄrence in diÄrence' estimator. The second, relates to a model based ex-ante evaluation. We present the conditions for each to provide a reliable evaluation and Å some of the crucial parameters using data from the British Labour Force Survey. We stress that the success of this type of labour market programmes hinge on dynamic aspects of the youth labour market, in particular the pay-off to experience and training.
Keywords: H53; J21; 330